The Reform of the Transparency Directive. Minimum or Full Harmonisation of Ownership Disclosure? - Fleischer, Holger; Schmolke, Klaus Ulrich (European Business Organization Law Review, 2011)
The reform of the Transparency Directive is presently on the political agenda, with one of the key questions focusing on the level of harmonisation: should the current minimum harmonisation be retained or is a move towards full harmonisation advisable? After confirming legal competence for the full harmonisation of European capital markets law, this article weighs the pros and cons of full harmonisation in the case of ownership disclosure rules. The ability to overcome the costly legal fragmentation of the current regulatory regime for notification of major shareholdings throughout Europe is revealed as the greatest benefit of full harmonisation. As full harmonisation not only reduces compliance costs but also boosts investor confidence, all market participants stand to benefit. Despite this, full harmonisation also carries certain costs as it inhibits regulatory competition, increases complexity in implementing EU law in national legal systems and carries the danger of a petrification effect. The article reveals that these cost factors are not sufficient to undermine the case for full harmonisation for financial instruments requiring notification, as well as for thresholds, timeframes and notification formats. It goes on to show that legal regimes can retain their adaptive efficiency by allowing them to conduct temporary legislative experiments. However, the article refrains from generalising this finding, encouraging a targeted full harmonisation approach for the Transparency Directiv
Keywords: Transparency Directive; Disclosure; Ownership Disclosure; Harmonisation; Minimum Harmonisation; Full Harmonisation